PENGARUH CORPORATE GOVERNANCE DAN AUDITOR EKSTERNAL TERHADAP INTEGRITAS LAPORAN KEUANGAN (Perusahaan Manufaktur yang terdaftar di BEI pada Periode 2008-2011) - Putri Intan Amalia, 09.05.52.0159; Sri Mindarti, Ceacilia (Students Journal of Accounting and Banking, 2013)
This study aims to examine how the effect of institutional ownership, independent commissioners, the audit committee and external auditor to the integrity of the financial statements. Study sampleas many as 101 manufacturing companieson the Indonesian Stock Exchange, and the method use dispurposive sampling is a sampling method by specifying certain criterias with the method of pooling data (2008 - 2011), so the number of samples (n) =404. Methods of data collection using documentationâs method of Indonesian Stock Exchange. And the method of data analysis using multiple linear regression. The results showed that institutional ownership is not significant to the integrity of the financial statements partially, the independent commissioner is not significant to the integrity of the financial statements partially, the audit committee is not significant to the integrity of the financial statements and auditor external is not significant to the integrity of the financial statements partially.Keywords: institutional ownership, independent commissioner, audit committee, auditor external and integrity of the financial statements.